(untitled) (Journal Of Educational and Psychological Researches, 2018)
Educational and psychological adjustment considered to be one of the effective and serious matters at people dealings and behaviors. Generally, psychological adjustment reflects positively on an individual mental health and their capability to be creative at their field. In contrast to those people who lack this feature. As for educational adjustment, it refers to the compatibility and harmony between an individuals and people around. Thus, these features should be available among students particularly those who stay in students’ hostel since they live far from their families. The findings of study revealed that there is Educational and psychological adjustment between male and female. Besides, significant differences were showed between male and female based on the outcomes.